Child poverty, child maintenance and interactions with social assistance benefits among lone parent families: A comparative analysis - Mia Hakovirta; Christine Skinner; Heikki Hiilamo; Merita Jokela (Luxembourg Income Study (LIS), 2019)
In many developed countries lone parent families face high rates of child poverty. Among those lone parents who do get child maintenance there is a hidden problem. States may retain all, or a proportion, of the maintenance that is paid in order to offset other fiscal costs. Thus, the potential of child maintenance to alleviate poverty among lone parent families may not be fully realized, especially if the families are also in receipt of social assistance benefits. This paper provides an original comparative analysis exploring the effectiveness of child maintenance to reduce child poverty among lone parent families in receipt of social assistance. It addresses the question of whether effectiveness is compromised once interaction effects (such as the operation of a child maintenance disregard) are taken into account in four countries Australia, Finland, Germany and the UK using the LIS dataset (2013). It raises important policy considerations and provides evidence to show that if policy makers are serious about reducing child poverty, they must understand how hidden mechanisms within interactions between child maintenance and social security systems can work as effective cost recovery tools for the state, but have no poverty reduction impact.
Keywords: 330